96.4k views
22 votes
If g(x)=x^2-x, what is g(x+2)? please explain step by step

User AthibaN
by
4.7k points

2 Answers

12 votes

Answer:

g(x)=x^2

Explanation:

g(x+2)=x^2+4x+4-(

x+2)

=x^2+5x+6

User Sherein
by
5.0k points
8 votes

Answer:

Since g(x+2)

the equation would become g(x-2) = (x+2)^2- (x+2)

Simplify

(x+2)^2 - (x+2)

(x+2)(x+2) - (x+2)

FOIL : (x^2 + 2x + 2x + 4) - (x+2) *dont forgot you need to distribute the negative in the next step*

x^2 + 4x + 4 - x - 2

Like terms : x^2 + 3x + 2

So g(x+2) = x^2 + 3x + 2

User Robert Wildling
by
4.7k points